"Worn, loved, let go": A phenomenological study of fashion disposal among Muslim women - Rosely, Nurhidayah; Abdullah Than, Ayu Kamareenna; Ismail, An Nur Nabila; Nik Mohd Zainordin, Nik Mohamad Shamim (Journal of Islamic, Social, Economics and Development, 2025)
The rise of fast fashion has intensified impulsive purchasing and accelerated product turnover, leading to growing concerns over clothing disposal and environmental waste. Despite awareness of sustainability, many consumers continue to engage in rapid consumption and discard fashion items prematurely. Among Muslim women, these behaviours present a unique tension, as Islamic values emphasize moderation (wasatiyyah), responsibility (amanah), and avoidance of waste (israf). This study explores how young adult Muslim women negotiate this tension through their fashion disposal behaviour and how they reconcile the psychological dissonance arising from overconsumption. Guided by Cognitive Dissonance Theory (Festinger, 1957) and employing a phenomenological approach, in-depth interviews uncovered four emerging themes. The theme of sustaining value beyond possession demonstrated proactive, value-driven disposal through donation, resale, or gifting, viewing these acts as ethical extensions of utility. The theme of strategic minimizers displayed functional and delayed disposal patterns centred on practicality and item longevity. The theme of sunk cost rationalisation framed disposal as a structured cognitive process to justify wardrobe renewal and reduce guilt, while the theme of self-compensation exhibited emotionally avoidant disposal rooted in self-gratification and attachment. These findings reveal that fashion disposal among Muslim women is not merely functional but a morally and emotionally charged process influenced by internalized values and psychological coping mechanisms. While practices like donation reflect moral alignment, they may also perpetuate cycles of excessive consumption. This study advances understanding of faith-based sustainable fashion behaviours, emphasizing the need for culturally grounded interventions that address emotional, ethical, and cognitive dimensions of consumption and disposal.